Bio-Prospecting Locally Relevant Industrial Yeast Strains from Fermented Carbohydrate-Rich Food Waste from Nigeria - Kazeem, Muinat Olanike; Olabamiji, Samson Oluwatosin; Ajijolakewu, Kamoldeen A.; Hafid, Halimatun Saadiah (Iraqi Journal of Science, 2025)
Nigerian fermented food is characterized by high carbohydrate concentration. Widely spread yeast strains in the local fermented food waste amass traits useful to biofuel industry. This study aims to identify, characterize and assess the level of stress tolerance of local yeast strains residing in food waste produced from Nigerian "fufu," a fermented cassava product. Through the use of morphological, cellular, and amplification of TS1/ITS4 and D1/D2 rDNA sequencing, the yeast strains were identified. To test the yeast strains’ resilience to stress, different concentrations of ethanol (15% - 20%v/v), sugar (5% - 25%w/v), and temperatures (30°C - 45°C) were applied. Out of the eight yeast strains, the isolate Y4, also known as Kazachstania pseudohumilis Y4 (Accession number: ON876535:1), was most promising since it could withstand ethanol at 15% and 20% (v/v). The strain showed tolerance to glucose at 20% (w/v) and temperatures (30°C-45°C). The carbohydrate-rich fermented food waste was a valuable source of stress-tolerant yeast, a vital resource for the bioethanol industry.